Badiou and American Modernist Poetics - MacKenzie, Cameron (Pivotal Studies in the Global American Literary Imagination, 2018)
Badiou and American Modernist Poetics explores the correspondence between Alain Badiou's thinking on art and that of the canonical modernists T.S. Eliot, Wallace Stevens, and Ezra Pound. Utilizing a multidisciplinary approach, the text engages with themes of the void, mastery, and place present in both modernist poetry and in Badiou's philosophy. Through an examination of classic modernist texts, Cameron MacKenzie reveals that where Badiou hopes to go, the modernists have already been.